Innovative Business Models and IoT-Driven Solutions for Smart Goat Farming Management - Junaedi, Achmad Tavip; Renaldo, Nicholas; Susanti, Wilda; Tendra, Gusrio; Jahrizal, Jahrizal; Dalil, M.; Veronica, Kristy; Suhardjo, Suhardjo; Musa, Sulaiman; Cecilia, Cecilia (Interconnection: An Economic Perspective Horizon, 2024)
This study examines how farmers can transition from traditional practices to a more data-centric approach, using IoT not just for operational efficiency but also as a strategic tool for creating new revenue streams. This research introduces the concept of smart goat farming ecosystems, where IoT technology, data analytics, and business model innovation converge to create a comprehensive and sustainable farm management approach. The qualitative research design will be used to understand the complex and context-dependent nature of IoT adoption in goat farming. This research has demonstrated that the integration of Internet of Things (IoT) technologies in goat farming has the potential to significantly improve operational efficiency, animal welfare, and productivity. The use of IoT devices for real-time health monitoring, automated feeding systems, and environmental control can assist farmers in optimizing resources, reducing waste, and ensuring better care for livestock. Future study can explore how IoT can be combined with artificial intelligence, blockchain, and big data analytics to enhance decision-making and operational efficiency in livestock farming.